Traffic Accident Analysis in Prosses Evidence in Traffic Accidents Based on Act No. 22 of 2009 - Rudiana Eka Pramana Putra; Akhmad Khisni (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Proof play an important role in the process of examination of the court, the development progress in the field of information technology and telecommunications, also developed the theories and practices of the use of evidence outside of a predetermined in the procedural law in Indonesia The problems of this study are: traffic accident analysis methods in the process of proving the traffic accident under the Act No. 22 of 2009. Obstacles and solutions in traffic accident analysis methods in the process of proving the traffic accident under the Act No. 22 of 2009.The research approach used adalan normative research. Empirical normative legal research. Data obtained from the study will be analyzed using qualitative methods of normative analysis.Based on this study, the result that the completion of a traffic accident encountered on the streets and certain times and considered as a routine activity, because over the task of administrative services in the field of vehicle or driver in addition to the public discipline road users is still very low. If there is no presence of members of the Police / Traffic Police physically there is a tendency offense by violating traffic signs. So for the purpose of realizing Kamseltibcar Kudus Resort Police and increased professionalism Police Traffic Accident Analysis required implementation by implementing the handling of traffic accident right scene.Keywords: Law Enforcement; Criminal Law Advisory; Traffic Accident Analysis Proof of Traffic Accidents.